2006
DOI: 10.1007/s00441-006-0288-z
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of excitatory central synapses: from structure to function

Abstract: Synapses are the key elements for signal transduction and plasticity in the brain. For a better understanding of the functional signal cascades underlying synaptic transmission, a quantitative morphological analysis of the pre- and postsynaptic structures that represent morphological correlates for synaptic transmission is important. In particular, realistic values of the number, distribution, and geometry of synaptic contacts and the organization of the pool of synaptic vesicles provide important constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 96 publications
8
69
1
1
Order By: Relevance
“…Recent work by Lefort et al (2009) has also revealed high-amplitude synaptic connections in all types of neurons in the somatosensory column producing EPSPs up to 7.8 mV, which are important in driving the network to fire. It is also the case that synaptic connections between cortical neurons can form clusters of two to five closely spaced synaptic contacts per site (Rollenhagen and Lübke, 2006). Based on these anatomical and physiological data, the presynaptic innervation pattern assumption of our model, in which relatively strong unitary connections are mapped to specific branches, is a reasonable description of an important subset of the presynaptic input to pyramidal neuron basal dendrites.…”
Section: Late Depression Of Nmda Spike Responsesmentioning
confidence: 80%
“…Recent work by Lefort et al (2009) has also revealed high-amplitude synaptic connections in all types of neurons in the somatosensory column producing EPSPs up to 7.8 mV, which are important in driving the network to fire. It is also the case that synaptic connections between cortical neurons can form clusters of two to five closely spaced synaptic contacts per site (Rollenhagen and Lübke, 2006). Based on these anatomical and physiological data, the presynaptic innervation pattern assumption of our model, in which relatively strong unitary connections are mapped to specific branches, is a reasonable description of an important subset of the presynaptic input to pyramidal neuron basal dendrites.…”
Section: Late Depression Of Nmda Spike Responsesmentioning
confidence: 80%
“…It was shown in several studies that morphological parameters of synaptic boutons (size and shape of boutons; number of postsynaptic targets; number, arrangement and size of active zones; number and size of mitochondria; presence of dense core vesicles etc.) can correlate well with their physiological properties (Kubota and Kawaguchi, 2000;Telgkamp et al, 2004;Rollenhagen and Lübke, 2006;Bodor et al, 2008;Yoshida et al, 2011;Holderith et al, 2012). After 3-dimensional reconstruction of perisomatic boutons, we measured these parameters to allow a comparison to their different functional properties and found that differences among interneuron types are manifested even in the finest ultrastructural details of their terminals possibly reflecting the adjustment of the signalling and vesicular release machinery to the requirements of the activity pattern.…”
Section: Introductionmentioning
confidence: 97%
“…During the last several decades, a great deal of information has been obtained on the structure, molecular make up, and physiological function of synapses; yet synapses are morphologically and molecularly highly diverse depending on the pre and postsynaptic parent neurons 4 . Only for a handful of synapse types were structure-function studies accomplished so far [5][6][7] . This was mostly due to technical constrains that prevented a precise identification of the nature of the pre-and postsynaptic elements.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural analysis has provided critical insights into the variability of postsynaptic membrane specializations across distinct synaptic contacts both in terms of synaptic size and content in neurotransmitter receptors 6 , which has a large impact on the strength and plasticity of synaptic transmission. Furthermore, a large body of research indicates that the number of ionotropic glutamate receptors expressed at different types of synapse is regulated in an afferent-and target-dependent fashion [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%